KEMAMPUAN TANAH HUTAN MANGROVE SEBAGAI SUMBER ENZIM DALAM HIDROLISIS ENZIMATIK SUBSTRAT SEKAM PADI - Widayantini, Ni Luh Md.; Wirajana, I Nengah; Suarya, Putu (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014DO - 10.24843/JCHEM.2014.v08.i01.p06, 2014)
Cellulase activity of mangrove forest soil from Suwung Kauh Beach in Bali has been reported in previous study. An enzymatic hydrolysis of rice husk with this mangrove forest soil as a source of enzymes was conducted. The aim of this study was to determine the ability of this mangrove forest soil as a source enzymes in hydrolyzing rice husk with and without delignification incubated in varied durations. The rice husk with and without delignification were mixed with mangrove forest soil  and incubated at pH 7 and  29 o C with a various incubation times of 0, 1, 2 , 3, and 4 weeks. Reducing sugar content of the results of incubation was measured by spectrophotometry using the Nelson-Somogyi method. The results of this study showed that the mangrove forest soil can hydrolyse the delignification rice husk, but could not degrade the rice husk without delignification. The highest reducing sugar content of 0,892 mg/100mL was resulted from hydrolysis of the delignification rice husk during one week. This result indicated that the mangrove forest soil as a source of cellulase had an ability in hydrolyzing the delignificated rice husk in pH 7 and 29 o C incubated in one week.
Keywords: rice husk, delignification, enzymatic hydrolysis, mangrove forest soil, reducing suga